Health-related quality of life and psychological distress among cancer survivors in a middle-income country - Subramaniam, Shridevi; Kong, Yek Ching; Chinna, Karuthan; Kimman, Merel; Ho, Yan Zheng; Saat, Nadiah; Malik, Rozita Abdul; Mohd Taib, Nur Aishah; Abdullah, Matin Mellor; Lim, Gerard Chin Chye; Tamin, Nor Saleha Ibrahim; Woo, Yin Ling; et al. (Wiley, 2018)
Objectives: Quality of life and psychological well-being are important patient-centered outcomes, which are useful in evaluation of cancer care delivery. However, evidence from low-income and middle-income countries remains scarce. We assessed health-related quality of life (HRQoL) and prevalence of psychological distress (anxiety or depression), as well as their predictors, among cancer survivors in a middle-income setting. Methods: Through the Association of Southeast Asian Nations Costs in Oncology study, 1490 newly diagnosed cancer patients were followed-up in Malaysia for 1 year. Health-related quality of life was assessed by using the European Organization for Research and Treatment of Cancer Quality of Life Questionnaire Core 30 (EORTC QLQ-C30) and EuroQol-5 (EQ-5D) dimension questionnaires at baseline, 3 and 12 months. Psychological distress was assessed by using Hospital Anxiety and Depression Scale. Data were modeled by using general linear and logistic regressions analyses. Results: One year after diagnosis, the mean EORTC QLQ-C30 Global Health score of the cancer survivors remained low at 53.0 over 100 (SD 21.4). Fifty-four percent of survivors reported at least moderate levels of anxiety, while 27% had at least moderate levels of depression. Late stage at diagnosis was the strongest predictor of low HRQoL. Increasing age, being married, high-income status, hospital type, presence of comorbidities, and chemotherapy administration were also associated with worse HRQoL. The significant predictors of psychological distress were cancer stage and hospital type. Conclusion: Cancer survivors in this middle-income setting have persistently impaired HRQoL and high levels of psychological distress. Development of a holistic cancer survivorship program addressing wider aspects of well-being is urgently needed in our settings.